The correlation between Children’s Age Factors toward the clinical manifestation and the severity level of COVID-19 in Bengkulu Province in 2020 - Dia Triyani Putri; Begumratu VOCA; Diah Ayu Aguspa Dita; Dessy Triana; Riry Ambarsari; Utari Hartati Suryani (UNIB PRESS, 2022)
Coronavirus Disease 2019 (COVID-19) is a disease that can infect people of all ages. Symptoms can range from asymptomatic to severe in certain age groups. It can occur due to differences in the innate immune response, comorbidities and the function, distribution, maturation of the SARS-CoV-2 receptor. This study aimed to determine the correlation between children’s age factors toward the clinical manifestation and the severity level of COVID-19 in Bengkulu Province in 2020. An observational analytic study with cross-sectional design was used in this study. This study included 86 children aged 0-18 years old who were confirmed positive for COVID-19 and lived in Bengkulu Province from March to December 2020. The clinical manifestation was assessed using the COVID-19 epidemiological investigation form and medical records from M.Yunus Hospital. The degree of severity is determined using Ministry of Health of Indonesia’s Guidelines for COVID-19 Prevention and Control. The result showed that of the majority of children aged 0-1 years old, 5-11 years old, and 12-18 years old have asymptomatic severity illness. While children are between the ages of two and four, the majority of their illnesses are of a mild severity. There was no significant correlation between children age factors and the severity of COVID-19 in Bengkulu Province in 2020.